Effects of Niacin Combination Therapy with Statin or Bile-Acid Resin on Lipoproteins and Cardiovascular Disease - Zambon, Alberto (2014)
Two large studies in populations selected for CVD demonstrated that raising HDL cholesterol with niacin added to statin therapy did not decrease CVD. We examine the association of lipoprotein subfractionswith niacin and changes in coronary stenosis and CVD event risk. One hundred and seven individuals from two previous studies using niacin in combination with either statin or bile acid binding resin were selected to evaluate changes in lipoproteins separated by density gradient ultracentrifugation to progression of coronary artery disease as assessed by quantitative coronary angiography. Improvement in coronary stenosis was significantly associated with the decrease of cholesterol in the dense LDL particles and across most of the IDL and VLDL particles density range, but, not with any of the HDL fraction or of the more buoyant LDL fractions. Event free survival was significantly associated with decrease in cholesterol of the dense LDL and IDL; there was no association with changes in cholesterol in the HDL and buoyant LDL fractions. Niacin combination therapy raises HDL cholesterol and decreases dense LDL and intermediate density lipoprotein cholesterol. Changes in LDL and IDL are related to improvement in CVD. Lipoprotein subfraction analysis should be performed in larger studies utilizing niacin in combination with statins.